New research findings on the mechanism through which tolerance to East Coast fever is mediated in cattle in Eastern, Central and Southern Africa - CGIAR Research Program on Livestock (2021)
End of research phase that generated new information on the mechanism through which tolerance to East Coast Fever (ECF) in cattle is mediated.